Do Immigrants Shield the Locals? Exposure to COVID-Related Risks in the European Union - Bossavie, Laurent; Garrote Sanchez, Daniel; Makovec, Mattia; Ozden, Caglar (World Bank, Washington, DC, 2020)
This paper investigates the relationship between immigration and the exposure of native workers to the health and labor-market risks arising from the COVID-19 pandemic. Using various measures of occupational risks based on European Union labor force survey data, the paper finds that immigrant workers, especially those from lower-income member countries in Eastern Europe or from outside the EU, face greater exposure than their native-born peers to both income and health-shocks related to COVID-19. The paper also shows that native workers living in regions with a higher concentration of immigrants are less exposed to some of the income and health risks associated with the pandemic. To assess whether this relationship is causal, a Bartik-type shift-share instrument is used to control for potential bias and unobservable factors that would lead migrants to self-select into more vulnerable occupations across regions. The results show that the presence of immigrant workers has a causal effect in reducing the exposure of native workers to various risks by enabling the native-born workers to move into jobs that could be undertaken from the safety of their homes or with lower face-to-face interactions. The effects on the native-born population are more pronounced for high-skilled workers than for low-skilled workers, and for women than for men. The paper does not find a significant effect of immigration on wages and employment — indicating that the effects are mostly driven by a reallocation of natives from less safe jobs to safer jobs.